Isolation, Purification and Pathogenicity Assessment of Fusarium oxysporum Schl. f.sp. ciceris Inciting Wilt Disease in Chickpea - Srinivas, Bhukya; Basha, S. Ameer; Sagar, B. Vidya; Kumar, C. V. Sameer; Reddy, G. Kiran (International Journal of Economic Plants, 2024)
The present study was conducted during rabi (November–March, 2022–23) at the Department of Plant Pathology and Central Instrumentation Cell, College of Agriculture, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad, Telangana, India to isolate, purify and pathogenicity assessment of Fusarium oxysporum Schl. f.sp. ciceris inciting wilt disease in chickpea. The pathogen was isolated from infected chickpea and purified, with its cultural and morphological characteristics utilized for identification. The analysis revealed that pathogen grown on potato dextrose agar media exhibited traits consistent with Fusarium oxysporum Schl. f.sp. ciceris, appearing as mycelium colour, texture, pigmentation, type and speed of growth as cultural characteristics and Fusarium oxysporum Schl. f.sp. ciceris as possessing macroconidia, microconidia and chlamydospore as morphological characteristics. Furthermore, a pathogenicity test was conducted on the chickpea cultivar JG-62, cultivated in pots under controlled conditions within a net house was successfully satisfying Koch’s postulates. Because of its great nutritious content, chickpeas have risen to prominence. where it plays a significant role in ensuring food security and sustainability. However, wilt disease in chickpea remains a persistent threat, leading to substantial losses in both quantity and quality. To address this issue the investigation provided valuable insights into understanding the pathogen, thereby contributing to the development of cost-effective solutions for managing wilt disease in chickpea which helps in increasing crop yield to the chickpea growing farmers of Telangana.